Snake as Symbol in the Prehistory of the Area of Croatia - Potrebica, Hrvoje (Array, 1998)
Snake appears as religious symbol as early as in the Neolithic. In the prehistoric period of the area of present Croatia, that phenomenon is especially visible in the religious culture of prehistoric Illyrian tribes. The Illyrian cult of the snake inspired Greek and other myths connected to these tribes. Even the name Illyria contains root illo that is closely connected to snake. The Greek legend says that Illyrians origin from Illyrios, the mythical son of Cadmus and Harmonia. The myth says that after his birth, a snake wrapped around him, and thus gave him all its magical powers. The symbolism of snake has been very complex. It appeared on coins as well as on ships, clearly illustrating its protective aspect. That aspect is closely connected to the snake as a symbol of healing. In that form, it is usually the attribute and follower of a god of medicine, as it is the case with the Greek god, Asclepius. It seems that similar deity has been worshipped on the eastern Adriatic coast in the pre-Roman times. That was a good base for later syncretism of that god with before mentioned Asclepius. Although we cannot yet document it with actual archaeological material, snake must have been closely connected to the chthonic principles. The proof of that lies in the very legend of Cadmus and Harmonia: in the moment of their departure from this world they were transformed to snakes. From their mythical forefathers, up to the historic times, snake had an important role in the religious world of Illyrians. It even survived the rise of Christianity, and in a transformed form, entered the culture of people that inhabited this area in later periods, as symbolic legacy of Illyrians. The remains of that ancient cult are still present in the concept of a snake as a grave protector and in the tattoos that some Catholic women in Bosnia wear on their arms.